THE INFLUENCE OF PERCEIVED TEACHER SUPPORT AND ACADEMIC BOREDOM ON STUDENT ENGAGEMENT AMONG STUDENT AT MUHAMMADIYAH VOCATIONAL HIGH SCHOOL IN SIDOARJO - Dhia Kesuma Q. R.; Ghozali Rusyid Affandi (Academic Journal Research, 2026)
Objective: This study aims to examine the influence of perceived teacher support and academic boredom on student engagement among vocational high school students in Sidoarjo. The study investigates how students’ perceptions of teacher support and experiences of academic boredom contribute to their behavioral, emotional, and cognitive engagement in learning. Method: This study employed a quantitative survey design involving 182 active students from grades X and XI of one vocational high school in Sidoarjo. Participants were selected using a convenience sampling technique. Data were collected through three instruments: the Student Engagement Scale (19 items), the Perceived Academic Teacher Support Scale (16 items), and the Academic Boredom Scale adapted from the Achievement Emotions Questionnaire (22 items). The data were analyzed using Pearson correlation and multiple linear regression with JASP software. Results: The findings revealed that perceived teacher support and academic boredom simultaneously had a significant effect on student engagement (F= 35.45, p < .001), explaining 28.4% of the variance in student engagement (R2= 0.284). Perceived teacher support positively and significantly predicted student engagement (β = 0.462, p < .001), while academic boredom negatively and significantly predicted student engagement (β = -0.198, p = .002). Correlation analysis further showed a positive correlation between perceived teacher support and student engagement (r = 0.496, p < 0.001) and a negative correlation between academic boredom and student engagement (r = -0.276, p < .001). Novelty: This study contributes to the educational psychology literature by simultaneously examining the roles of perceived teacher support and academic boredom in predicting student engagement among vocational high school students, a population that remains underrepresented in previous research. The findings provide empirical evidence highlight the importance of supportive teacher-student relationships and boredom reduction strategies to enhance engagement within vocational education settings.